Pengaruh Ukuran Perusahaan, Komite Audit Dan Opini Auditor Terhadap Audit Report Lag - Rochmah, Alfi Choirur; Nuraini, Fitri; Soedjono, Soedjono (JCA (Jurnal Cendekia Akuntansi), 2023)
Abstract Reliable financial reports must go through an audit process, but the length of time the audit can affect the timeliness in the issuance of financial statements so that it can cause the reduction of benefits for decision making. Therefore, the importance of timeliness in the submission of financial statements so that they can be used immediately in decision making. This study aims to determine the partial and simultaneous effect of company size, audit committee and auditor's opinion on audit report lag in property, real estate and building construction companies listed on the Indonesian stock exchange during 2014 to 2020. This research is an associative quantitative research. The sample in this study was determined by purposive sampling method, in order to obtain 42 companies for 7 years of observation. So the number of observations is 294 samples. The data analysis method used is multiple linear regression method. Based on the results of this study, it shows that company size has a significant positive effect on audit report lag with a significant value of 0.205 and the audit committee has a significant positive effect on audit report lag with a significant value of 0.006. Meanwhile, the auditor's opinion has no significant negative effect on audit report lag with a significant value of 0.305. Firm size, audit committee and audit opinion simultaneously have a significant effect on audit report lag with a significant value of 0.009. Keywords: Audit Report Lag, Company Size, Audit Committee, Auditor's Opinion